REKONSTRUKSI KURIKULUM PENDIDIKAN MULTIKULTURAL DI SEKOLAH DASAR: SEBUAH KAJIAN KRITIS - Jenia Ghaziah; Sukran, Sukran; Pajrin, Ahdia; Alhalim, Muhammad; Ulya, Syastri (Study program PGSD FKIP Universitas Bung Hatta, 2025)
This study critically explores the urgency of reconstructing the multicultural education curriculum in Indonesian primary schools as a response to the nation’s diverse sociocultural realities. Employing a qualitative approach through literature analysis, the research examines conceptual foundations, practical implementation, and challenges encountered in applying multicultural education at the elementary level. The findings indicate that the current curriculum remains predominantly cognitive-oriented, while affective dimensions such as tolerance, inclusivity, and empathy are insufficiently internalized. Teachers play a pivotal role as multicultural agents; however, limited pedagogical competence, inadequate institutional support, and the persistence of homogenizing educational paradigms pose significant barriers. Empirical evidence highlights a gap between the discourse of multicultural education and its actual practices in schools. Therefore, curriculum reconstruction should emphasize inclusive values, participatory learning strategies, and the cultivation of a school culture that appreciates diversity. The study concludes that reconstructing the multicultural education curriculum is not merely an academic necessity but a fundamental prerequisite for fostering a just, peaceful, and democratic Indonesian society.